BUSINESS PROCESS IMPROVEMENT PLAN IN OPERATIONAL LEAD TIME CONTROL OF SPAREPART BY OPTIMIZING DIGITAL TOOL AND DEALING WITH VENDOR IN PT TACI - Widhi Wahyuniarti; Anton Mulyono Azis (CV. Radja Publika, 2025)
The manufacturing industry, particularly the automotive sector, faces significant challenges in managing lead time for spare parts procurement, which impacts operational efficiency and cost-effectiveness. PT TACI, a company specializing in compressor production for vehicle air conditioning systems, encounters delay in the spare parts procurement process, affecting its production schedule. The purpose of this research is to analyze and improve the spare part procurement and operational lead time control processes at PT TACI. The study identifies barriers in the current processes, especially those related to technology, web integration, and supplier agreements. A qualitative approach was employed, consisting of in-depth interviews, focus group discussions, and direct observations with key personnel in PT TACI’s Part Tool Inventory Control (PTIC) department. The findings reveal that delays primarily arise from manual approval processes, inefficient data integration between IMS and EPS systems, and inconsistent supplier performance. The research also emphasizes the role of digital technology, particularly web-based integration and supplier agreements, in enhancing procurement efficiency. Based on Business Process Improvement (BPI) principles, this study proposes a set of recommendations, including the automation of the approval process, real-time system integration, improved supplier collaboration, and the simplification of routine procurement processes. The implications of this research suggest that digital system optimization and stronger supplier relationships can significantly reduce lead times and improve operational performance. Future research could explore advanced technologies like AI or Blockchain for further procurement process optimization.